Victor Turner’s Last Adventure - Schechner, Richard (Anthropologica, 2022)
In his later work, Victor Turner examined links among ritual process, brain structure and function, and play. He was moving toward a synthesis of sociobiology and humanist anthropology. However, these investigations concealed a "religious wish": a yearning to resolve by means of "faith" the apparently intractable question of the relationship between "culture" and "nature." Ritual can be mapped out as a thickening nexus of behaviors which originates in insects and eventually branches out into the more-or-less free forms of human social, religious, and aesthetic behaviors. When seen this way, ritual is both conservative and creative, with a distinctly human future which is just as definite as its ethological past. The meeting place of this past and future is the still-evolving human brain.